PENGEMBANGAN POLIURETAN BERBASIS CPO SEBAGAI LINER ADHESIVE - Heri BW,; Henny S; Geni R (Indonesian Journal of Aerospace, 2003)
In effort to increase the economic value of CPO (Crude Palm Oil), a research to use it as polyurethane raw material for the liner adhesive has been conducted. In order to get monoglyceride, CPO is glycerolized with glycerol, KOH is used as a catalyst and Pyridine solvent at 105 degree C for 4-8 hours. In the presence of isocyanate, such as TDI (Toluen Diisocyanate) monoglyceride as a diol becomes Polyurethane. Based on the adhesive strength test, this polyurethane polymer, produce a low conductivity and heat resistance up to 400 degree C(better quality compared with polyurethane to be used available in the local market). Therefore the polyurethane with CPO base a good potential material as a liner adhesive.